Synthesis and self-assembly of CO2-responsive dendronized triblock copolymers. Issue 42 (9th September 2015) - Huo, Meng; Ye, Qiquan; Che, Hailong; Sun, Mengzhen; Yuan, Jinying; Wei, Yen
Abstract : Dendronized amphiphilic block copolymers POEGMA- b -P(G n )- b -PDEAEMA were synthesized, and their self-assembly behavior could be regulated by the dendron generation, the type of common solvent, and CO2 -stimulus. Abstract : Stimuli-responsive morphology evolution of polymeric self-assemblies may serve as a model to promote the understanding of cellular shape transformation. Generally, the original morphology of these self-assemblies can be obtained through delicate regulation of the ratio of hydrophobic/hydrophilic polymer chains. Regretfully, less attention has been paid to the influence of chain "thickness" on the self-assembly and stimuli-responsiveness. In this article, CO2 -responsive dendronized triblock copolymers POEGMA- b -P(G n )- b -PDEAEMA ( n = 1, 2) with Fréchet-type poly(aryl ether) as the dendron (G n ) were synthesized by RAFT polymerization, and the dendronized block was designed to allow the chain "thickness" tunable. We found that the generation of dendrons, the type of common solvent, and CO2 -stimulus all contributed to the self-assembly of these triblock copolymers. Micelles with different sizes could be obtained in both THF/H2 O and DMF/H2 O, except that POEGMA- b -P(G2)- b -PDEAEMA precipitated in THF/H2 O. Upon CO2 aeration, POEGMA- b -P(G1)- b -PDEAEMA micelles in THF/H2 O disrupted into smaller ones while in DMF/H2 O they swelled slightly. Micelles formed in DMF/H2 O of POEGMA- b -P(G2)- b -PDEAEMA were much larger than that of POEGMA- b -P(G1)- b -PDEAEMA. Similarly, POEGMA- b -P(G2)- b -PDEAEMA micelles swelled to larger micelles upon CO2 triggering. Considering the tunable thickness of the dendron block, these CO2 -responsive dendronized polymers may add a new dimension in biomimetic morphology transformation.